A Pécsi Tanítóképző megjelenése a századforduló pécsi sajtójában = Appearance of the female teacher training institute of Pécs in the Pécs press at the turn of the century - Takács, Zsuzsanna Mária (Közép-Európai Közlemények, 2018)
The lecture puts the time of the founding of the female teacher training institute of the Notre Dame Female Canon Order in Pécs and the following years into focus, in the light of the writings in the local newspaper. The institute was the oldest founded school in the region and thus filled a central role in female education. The examination of the periodicals, newspapers appeared in the first half of the 20th century can enrich the education-, social-as well as local history knowledge with such information that help us to deepen our knowledge by tincturing our earlier knowledge in connection with the micro history of the era. During the research we are going to examine the articles appeared in Pécsi Napló, Pécsi Közlöny, Pécsi Újság and Néptanoda, the official newspaper of the Association of the Female Teachers of Pécs in 1894-1895, on the basis of the viewpoints that how many writings were published in connection with the female teachers and their trainings and what characteristics these writings had in the judgement of this newest school type established for girls and the appearance of women in the teaching field.